SEM-ANN analysis of the social prescription of nature, physical activity, and healthy living initiatives for cardiovascular health: mediating role of social support - Menhas, Rashid (Frontiers in Public Health, 2025)
BackgroundCardiovascular diseases (CVDs) are a major public health concern, contributing significantly to morbidity and mortality. Several lifestyle factors, such as physical inactivity and poor eating habits, are essential for the onset and progression of cardiovascular diseases. A social prescription is an approach in which healthcare providers recommend nature-based activities, physical exercise, and healthy living programs to patients with cardiovascular disease as part of their treatment plan.ObjectiveThis study aimed to investigate the relationship between social prescription of nature, engagement in physical activity, participation in healthy living initiatives, and cardiovascular health, focusing on the mediating role of social support.MethodsThis cross-sectional study was conducted across China. A stratified sampling approach was used to collect primary data from the target population. A total of 5,600 participants were selected from the target population. The collected data were analyzed using structural equation modeling and artificial neural network approaches.ResultsBased on the structural model's bootstrapping, route analysis results demonstrated that each proposed path was significant. The findings revealed strong relationships between these variables, underscoring the importance of social support as a mediator in promoting cardiovascular health through nature exposure, physical activity, and healthy living initiatives. Sensitivity analysis using artificial neural networks revealed that NSP (117.73%) and PaSP (102.50%) were the most significant predictors, followed by HLISP (100%).ConclusionHealthcare professionals and policymakers can enhance cardiovascular health outcomes and contribute to the overall well-being of individuals by integrating nature-based interventions, promoting physical activity, and implementing healthy-living initiatives with targeted social support mechanisms.